2017
DOI: 10.1002/bin.1510
|View full text |Cite
|
Sign up to set email alerts
|

Application of multiple baseline designs in behavior analytic research: Evidence for the influence of new guidelines

Abstract: The multiple baseline (MBL) design is a single‐case experimental design that has both research and applied utility. Although the concurrent and nonconcurrent MBL variants are valid designs, each rules out different threats to internal validity. To help clarify these differences, studies have provided guidelines for graphically depicting and distinguishing between concurrent and nonconcurrent MBLs. This study assessed the extent to which data‐presentation guidelines have been adopted by examining single‐case ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…A non‐concurrent multiple baseline design (Coon & Rapp, ; Hammond & Gast, ) was adopted to demonstrate the relation between game‐based intervention and the ability to use an ATM independently. The experiment comprised three phases: (a) a baseline phase, in which sessions were performed to collect baseline data on the participants; (b) an intervention phase, in which the gaming system was used for training; and (c) a maintenance phase, which was conducted 2 weeks after the intervention was finished and assessed the continued performance of the participants.…”
Section: Methodsmentioning
confidence: 99%
“…A non‐concurrent multiple baseline design (Coon & Rapp, ; Hammond & Gast, ) was adopted to demonstrate the relation between game‐based intervention and the ability to use an ATM independently. The experiment comprised three phases: (a) a baseline phase, in which sessions were performed to collect baseline data on the participants; (b) an intervention phase, in which the gaming system was used for training; and (c) a maintenance phase, which was conducted 2 weeks after the intervention was finished and assessed the continued performance of the participants.…”
Section: Methodsmentioning
confidence: 99%
“…In behavior analysis, researchers and practitioners typically use single-case designs such as the reversal design, the alternating-treatment design, and the multiple baseline design to demonstrate experimental control Horner et al, 2005;Kratochwill et al, 2010). Among these designs, researchers have found that multiple baseline designs were the most frequently used (Coon & Rapp, 2018;Shadish & Sullivan, 2011;Smith, 2012). In contrast with other single-case designs, the multiple baseline design does not require the withdrawal of the treatment or the establishment of a criterion to be gradually changed, which may explain its predominant use in single-case research (Baer et al, 1968;Kratochwill & Levin, 2014).…”
Section: How Many Tiers Do We Need? Type I Errors and Power In Multipmentioning
confidence: 99%
“…Third, when needed, we evaluated the effects of BST on each participant's appropriate posture, smiling, and fidgeting. We evaluated the extent to which BST increased appropriate answers and appropriate questions using a nonconcurrent multiple baseline design across students (e.g., Carr, 2005;Coon & Rapp, 2018;Watson & Workman, 1981). As a secondary analysis, we fitted data for smiling, appropriate posture, and fidgeting to a concurrent multiple baseline across behaviors design for each student 2 (e.g., Carr, 2005).…”
Section: Experimental Designmentioning
confidence: 99%